UPAYA MENINGKATKAN KEMAMPUAN GURU DALAM MENGEFEKTIFKAN PEMBELAJARAN MELALUI PROGRAM PEMBINAAN PROFESIONAL GURU DAN SUPERVISI KELAS DI SD NEGERI 01 TALAWI MUDIK - Syamsulastri Syamsulastri (STKIP Pesisir Selatan, 2019)
This study aims to improve the ability of teachers to make learning effective through the teacher professional development program and class supervision at SD Negeri 01 Talawi Mudik in the 2017/2018 academic year. This research is classified as a school action research involving 10 teachers who need to be enhanced in their ability to effectively manage their learning. The study was conducted in three cycles and each cycle consisted of four stages: planning, implementing, observing and reflecting. The specified performance indicators are: if there is an increase in the ability to effectively manage learning. From the analysis it was found that there was an increase in the ability to make effective the management of learning in the first cycle which obtained an A value of 24.24% B value of 25.76% and a C value of 50%, in the second cycle which obtained an A value of 50% a value of B of 40.91% and C value of 9.09%, while in cycle III who obtained an A value of 65.15% B value was 34.85% and C value was 0%. Thus it can be concluded that through the Professional Development program the teacher can Improve the Ability of Teachers in Making Learning Effective. Thus it can be suggested to supervisors or other researchers that through the Professional Coaching program the teacher can be used as an alternative in improving the Teacher's Ability to Effectively Learning.